Training on systematic review methods - Chakraborty, Shreya; Mukherji, Aditi (CGIAR Initiative on Transforming Agrifood Systems in South Asia, 2022)
The One-CGIAR initiatives for Mitigate+: Research for Low-Emission Food Systems (Mitigate+) and Transforming Agrifood Systems in South Asia (TAFSSA) jointly organised a virtual training workshop on Systematic Review Methods for CGIAR scientists to build capacities in concepts and tools of evidence synthesis. The workshop covered a 12-hour course module in 3-hour sessions across four days from across CGIAR centres, particularly focussed on scientists and researchers working on systematic scoping reviews. This was organized considering that multiple systematic scoping reviews had been planned or were ongoing in the two host initiatives as well as other CGIAR initiatives, making this effort for capacity building of researchers timely.